Improving Students' Ability in Developing Mutual Respect Character Through Problem Based Learning Model in Islamic Education Learning - Sari, Nilam; Irwanto, Andri; Supariati (Jurnal Pendidikan Profesi Guru, 2023)
This study aims to improve students' ability to develop a character of mutual respect in Islamic Education Through the Problem Based Learning Model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained using test and observation techniques. Tests are used to improve students' ability to develop a character of mutual respect and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that Learning Through the Problem Based Learning Model can improve student learning outcomes. This can be seen from the increase in the percentage of completeness of improving students' ability to develop a character of mutual respect in each cycle with details of the pre-cycle 45.54%, the first cycle 78.57% and in the second cycle increased to 89.57%. Thus, learning Through the Problem Based Learning Model can be used as an alternative to improve student learning outcomes.